Perseverance of social theories the role of explanation in the persistence of discredited information - Anderson, Craig A.; Lepper, Mark R. (1980)
The perseverance of social theories was examined in two experiments within a debriefing paradigm. Subjects were initially given two case studies suggestive of either a positive or a negative relationship between risk taking and success as a firefighter. Some subjects were asked to provide a written explanation of the relationship; others were not. In addition, experimental subjects were thoroughly debriefed concerning the fictitious nature of the initial case. Subsequent assessments of subjects' personal beliefs about the relationship indicated that even when initially based on weak data, social theories can service the total discrediting of that initial base. Both correlational and experimental results suggested that such unwarranted theory perseverance may be mediated, in part, by the cognitive process of formulating causal scenarios or explanations. Normative issues and the cognitive processes underlying perseverance were examined in detail, and possible techniques for overcoming unwarranted theory perseverance were discussed.